2011
DOI: 10.1245/s10434-011-1907-9
|View full text |Cite
|
Sign up to set email alerts
|

Lobular Breast Cancer: Same Survival and Local Control Compared with Ductal Cancer, but Should Both Be Treated the Same Way? Analysis of an Institutional Database over a 10-Year Period

Abstract: Although ILC is more often multicentric, bilateral, and associated with a positive margin of resection, local control and survival are similar to IDC. ILC can be treated similarly to IDC with good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 54 publications
3
49
3
3
Order By: Relevance
“…Regarding tumor characteristics, this study found that ILC had an increased prevalence of hormone receptor positivity/HER2 negativity, which has been described before [3,4,5,6,7,9,12,15,21,22,23]. ILC was also more likely to be mammographically occult with a false-negative rate of 6.8% in our study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding tumor characteristics, this study found that ILC had an increased prevalence of hormone receptor positivity/HER2 negativity, which has been described before [3,4,5,6,7,9,12,15,21,22,23]. ILC was also more likely to be mammographically occult with a false-negative rate of 6.8% in our study.…”
Section: Discussionsupporting
confidence: 85%
“…It should be noted that in the Pestalozzi et al [12] study of 767 ILC cases, an early advantage in DFS (16% lower event incidence) was observed for the ILC patients, followed by a late advantage for IDC patients after 6 years (54% higher incidence of events for ILC patients). Similar results for OS have been documented, with the majority of studies revealing no difference between the groups at 5 and 10 years [6,7,8,15,21,22,25]. Cristofanilli et al [7] found improved OS for ILC patients at 70 months, while Pestalozzi et al [12] found that ILC patients had an early advantage in OS (16% lower risk of death) but that IDC patients again had a late advantage after 10 years (50% higher risk of death for ILC patients).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This is also true when the mRNA expression profile-based molecular portraits classification of invasive breast cancer including the luminal A, luminal B, normal, HER2-positive, and basal-like (typically "triple negative") nomenclature has been used to classify the tumors (2). In drug development, strategies have approached invasive ductal and invasive lobular breast carcinomas as essentially the same disease (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…This histologic distinction is not an independent prognostic factor for patient outcome [41-43]. Allowing for variants, in general invasive lobular carcinoma is associated with a higher nodal stage (13.1 vs. 4.5%), higher absolute number of positive nodes, and higher ratio of positive nodes than invasive ductal carcinoma [44].…”
Section: Resultsmentioning
confidence: 99%